Accelerated 3D multi‐channel B1+ mapping at 7 T for the brain and heart - Kent, James L.; de Buck, Matthijs H. S.; Dragonu, Iulius; Chiew, Mark; Valkovič, Ladislav; Hess, Aaron T. (Magnetic resonance in medicine, 2024)
PurposeTo acquire accurate volumetric multi‐channel B1+$$ B_1^{+} $$ maps in under 14 s whole‐brain or 23 heartbeats whole‐heart for parallel transmit (pTx) applications at 7 T.Theory and MethodsWe evaluate the combination of three recently proposed techniques. The acquisition of multi‐channel transmit array B1+$$ B_1^{+} $$ maps is accelerated using transmit low rank (TxLR) with absolute B1+$$ B_1^{+} $$ mapping (Sandwich) acquired in a B1+$$ B_1^{+} $$ time‐interleaved acquisition of modes (B1TIAMO) fashion. Simulations using synthetic body images derived from Sim4Life were used to test the achievable acceleration for small scan matrices of 24 × 24. Next, we evaluated the method by retrospectively undersampling a fully sampled B1+$$ B_1^{+} $$ library of nine subjects in the brain. Finally, Cartesian undersampled phantom and in vivo images were acquired in both the brain of three subjects (8Tx/32 receive [Rx]) and the heart of another three subjects (8Tx/8Rx) at 7 T.ResultsSimulation and in vivo results show that volumetric multi‐channel B1+$$ B_1^{+} $$ maps can be acquired using acceleration factors of 4 in the body, reducing the acquisition time to within 23 heartbeats, which was previously not possible. In silico heart simulations demonstrated a RMS error to the fully sampled native resolution ground truth of 4.2° when combined in first‐order circularly polarized mode (mean flip angle 66°) at an acceleration factor of 4. The 14 s 3D B1+$$ B_1^{+} $$ maps acquired in the brain have a RMS error of 1.9° to the fully sampled (mean flip angle 86°).ConclusionThe proposed method is demonstrated as a fast pTx calibration technique in the brain and a promising method for pTx calibration in the body.